PELATIHAN BUSINESS MODEL CANVAS (BMC) BAGI PARA PEMILIK USAHA KECIL DI SABU RAIJUA, NUSA TENGGARA TIMUR - Kempa, Sesilya; Sahetapy, Wilma Laura; Suprapto, Widjojo; Palumian, Yonathan; Andreani, Fransisca (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2025)
This community service activity is aimed at entrepreneurs who are members of the PPA Sabu Raijua. Field observations revealed a lack of understanding regarding the business model that suits their business conditions. Many entrepreneurs in the group have an inaccurate concept of their product potential, customer mapping, and financial management, which hampers the development of their businesses and the improvement of their economic well-being. Training and mentoring on developing a business model using the Business Model Canvas (BMC) focused on changing the mindset and behavior in managing micro and small enterprises. After conducting financial health tests and visiting each business, the main theme of the training was the development of a new business model following the BMC guidelines. The training resulted in the creation of a new business model. Mentoring was provided to support the implementation of this new model in the micro-enterprises of the members. The impact of the training and mentoring was evident in the increased income of the micro and small businesses managed by the members of the PPA Sabu Raijua